Optimal Timing and Tilting of Equity Factors. Issue 4 (2nd October 2019) - Dichtl, Hubert; Drobetz, Wolfgang; Lohre, Harald; Rother, Carsten; Vosskamp, Patrick
Abstract : Aiming to optimally harvest global equity factor premiums, we investigated the benefits of parametric portfolio policies for timing factors conditioned on time-series predictors and tilting factors based on cross-sectional factor characteristics. We discovered that equity factors are predictably related to fundamental and technical time-series indicators and to such characteristics as factor momentum and crowding. We found that such predictability is hard to benefit from after transaction costs. Advancing the timing and tilting policies to smooth factor allocation turnover slightly improved the evidence for factor timing but not for factor tilting, which renders our analysis a cautionary tale on dynamic factor allocation. Abstract : Disclosure: Two of the authors are at Invesco, one is at Allianz Global Investors. The authors follow an evidence-based investment process, including multi-factor equity propositions. Therefore, Invesco and Allianz Global Investors have a commercial interest in the subject matter (optimal equity factor allocation). Editor's note Submitted 23 November 2018 Accepted 28 June 2019 by Stephen J. Brown This article was externally reviewed using our double-blind peer-review process. When the article was accepted for publication, the authors thanked the reviewers in their acknowledgments. David Blitz and Mike Sebastian were the reviewers for this article.